The empirical study of green buildings (residential) implementation: perspective of house developers - Mohamed Elias, Ezanee; Chong, Khai Lin (Elsevier B.V., 2015)
This paper presents a study of green buildings implementation from the perspective of housing developers.The agenda of green buildings is to preserve all natures from the destruction by human activities. However, not many of house owners know that their houses are degraded and produced CO2, roughly 10 to 30 tonnes annually.This means that our houses are one of the causes of the global warming and environmental pollution.Therefore, the green building concept for green residential is an alternative effort to decrease the effects of CO2. Green residential means applying the houses with a minimum energy, water and natural resources that provide good air quality and reduce wastes. This qualitative study aims to explore the perceptions of housing developers towards green residential development.Presently, the demand for green residential is very low because buyers hesitate to pay 30% more costs for a green residential than a conventional house.The data collections for the study area are throughout face-to-face semi-structured interviews, photo collections, and some observations with housing developers. There are twenty-two respondents involved during the data collection period from two home and property exhibitions.The study finds that 77% of respondents are aware of the green residential concept.The other 23% of respondents realize about the green residential concept and the perceived benefits but indistinguishable. Government roles are significantly crucial for flourishing the development of green building and technologies into the housing projects.